Nutritional and phytochemical screening of Moringa oleifera leaf powder in aqueous and ethanol extract - Shakeela Khalid; Muhammad Arshad; Shahid Mahmood; Waleed Ahmed; Farzana Siddique; Waseem Khalid; Mehwish Zarlasht; Turky Omar Asar; Faten A. M. Hassan (International Journal of Food Properties, 2023)
Moringa oleifera has gained tremendous popularity in recent time due to its unlimited nutraceutical and functional properties. Present study was intended to investigate bioactive compounds present in Moringa oleifera leaf powder (MoLP). Moringa leaves were plucked, dried, ground, and were preliminarily analyzed for their proximate composition and mineral profile. Standard tests were conducted to evaluate flavonoids, alkaloids, saponins, proteins, amino acids, fats, and oils. Total phenolic content (TPC), total flavonoid content (TFC), total saponins content (TSC), total tannins content (TTC), FRAP assay, and DPPH radical scavenging property was also analyzed. Phytochemical investigation of Moringa oleifera leaf powder and its extract depicted the existence of rich bioactive compounds including amino acids, phenols, flavonoids, and saponins. The study illustrated that the phytochemicals in Moringa oleifera exhibit higher antioxidant activity against free radicals, revealing its strong nutritional worth.